Pemanfaatan Platform Quizizz Berbasis Game Based Learning Untuk Meningkatkan Minat dan Hasil Belajar Siswa Teknik Pemesinan di SMKS Pancasila Surakarta - Budiargo, Arif; Arifin, Adi Wahyu; Wijayanto, Danar Susilo; Suwarta, Suwarta (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2025)
Based on observations at SMKS Pancasila Surakarta, the learning process in Non- Conventional Machining Techniques, specifically the Basic Introduction to CNC Machines, faced challenges due to ineffective learning media, primarily relying on textbooks and lecture-based methods. This study aims to investigate the improvement in interest, activeness, and learning outcomes of class XI Machining Techniques (XI TPM) students through the application of the Quizizz platform based on game-based learning in the Merdeka Curriculum for the 2024/2025 academic year. The study employed a Classroom Action Research (PTK) approach with a quantitative Kemmis and Mc. Taggart model design. The research subjects were 13 students from class XI TPM. Data were collected through observation, learning outcome tests, questionnaires, and documentation. Data analysis included validation analysis, questionnaire analysis, observation sheet analysis, and learning outcome analysis. The results showed that in cycle I, student learning completeness reached 84.62% with an average score of 82.69, increasing in cycle II to 92.3% with an average score of 88.46. Student learning interest in cycle I reached 76.92%, increasing to 84.6% in cycle II. Student activeness in cycle I was 69.23%, rising to 92.3% in cycle II. Observation of student activeness in cycle I was 73%, increasing to 92% in cycle II. The application of the Quizizz platform based on game-based learning increased learning completeness by 69.23%, learning interest by 76.91%, and student activeness by 76.92%, indicating that students were more motivated and active in learning.